2020
DOI: 10.3389/fimmu.2020.575805
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies Against the Immunodominant Bullous Pemphigoid Epitopes Are Rare in Patients With Dermatitis Herpetiformis and Coeliac Disease

Abstract: Dermatitis herpetiformis (DH) is an extraintestinal manifestation of coeliac disease (CD). Patients with DH have an elevated risk of development of another autoimmune blistering skin disease, bullous pemphigoid (BP). In this study we investigated whether patients with DH and CD (mean age for both 49 years) have circulating autoantibodies against BP180, the major BP autoantigen. ELISA tests showed that only a few DH (3/46) and CD (2/43) patients had BP180-NC16A IgG autoantibodies. Immunoblotting found that more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(82 reference statements)
1
3
0
Order By: Relevance
“…Almost equal shares of BP180-NC16A ELISA positive and negative T2D+g and T2D samples recognized FL-BP180 in immunoblotting. Also 46% of the healthy control sera detected FL-BP180, which is in accordance with previous findings of our group and others ( 36 , 40 ). Our previous immunoblotting works have shown that FL-BP180 is frequently recognized by serum samples from patients with Alzheimer’s disease, multiple sclerosis, dermatitis herpetiformis and coeliac disease.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Almost equal shares of BP180-NC16A ELISA positive and negative T2D+g and T2D samples recognized FL-BP180 in immunoblotting. Also 46% of the healthy control sera detected FL-BP180, which is in accordance with previous findings of our group and others ( 36 , 40 ). Our previous immunoblotting works have shown that FL-BP180 is frequently recognized by serum samples from patients with Alzheimer’s disease, multiple sclerosis, dermatitis herpetiformis and coeliac disease.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous immunoblotting works have shown that FL-BP180 is frequently recognized by serum samples from patients with Alzheimer’s disease, multiple sclerosis, dermatitis herpetiformis and coeliac disease. Of note is that those samples displayed various proportions of BP180-NC16A ELISA positive and negative sera ( 28 , 30 , 36 ). The high proportion of FL‐BP180 recognition in immunoblotting could be explained by the fact that the Alzheimer’s disease and T2D populations tend to be older than those with the other conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations